Brasil sem imigrantes: Estimativas de longo prazo baseadas em microdados de paradigma - Leonardo Monasteiro; Daniel Lopes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper estimates the effect of non-Iberian immigration to Brazil based on historical and contemporary microdata. The historical base encompasses over 1.7 million immigrant records; the contemporary has more than 165 million records. The estimation of immigrant numeracy suggest that Stolz, Baten e Botelho (2013) underestimated their skills and, therefore, their impact on Brazil. An algorithm classified the surnames of contemporary Brazilians according to their ancestral origins. Two counterfactual estimates are constructed in order to estimate the income per capita if there had never been any non-Iberian immigration. The first counterfactual is built upon the regression of income on the percentages of each ancestral group in municipalities. The second, results from the regression of individual wages on the surname ancestry workers. The coefficients are used to estimate income in couterfactuals Brazils with no descendants of immigrants. It was estimated that in the absence of non-Iberian immigrants today's income would be from 12.6 % to 17 % lower.
Keywords: F22; O54; 330; immigration; human capital; numeracy